Emulsion polymerization of vinyl acetate using iodine‐transfer and RAFT radical polymerizations. Issue 3 (6th November 2012) - Nomura, Naoki; Shinoda, Keiji; Takasu, Akinori; Nagata, Kenji; Inomata, Katsuhiro
Abstract This study deals with control of the molecular weight and molecular weight distribution of poly(vinyl acetate) by iodine‐transfer radical polymerization and reversible addition‐fragmentation transfer (RAFT) emulsion polymerizations as the first example. Emulsion polymerization using ethyl iodoacetate as the chain transfer agent more closely approximated the theoretical molecular weights than did the free radical polymerization. Although 1H NMR spectra indicated that the peaks of α‐ and ω‐terminal groups were observed, the molecular weight distributions show a relatively broad range (Mw/Mn = 2.2–4.0). On the other hand, RAFT polymerizations revealed that the dithiocarbamate 7 is an excellent candidate to control the polymer molecular weight (Mn = 9.1 × 103, Mw/Mn = 1.48), more so than xanthate 1 (Mn = 10.0 × 103, Mw/Mn = 1.89) under same condition, with accompanied stable emulsions produced. In the Mn versus conversion plot, Mn increased linearly as a function of conversion. We also performed seed‐emulsion polymerization using poly(nonamethylene L‐tartrate) as the chiral polyester seed to fabricate emulsions with core‐shell structures. The control of polymer molecular weight and emulsion stability, as well as stereoregularity, is also discussed. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013